Penerapan perhitungan harga pokok produksi dengan menggunakan metode job order costing pada CV. Karya Wenang Manado - Rompas, Renaldo Noel Cristiano; Mawikere, Lidia M.; Lintong, Diana N. (Yayasan Widyantara Nawasena Raharja, 2025)
Accurate calculation of production costs is essential for determining the selling price and profitability of manufacturing companies. This study aims to examine the application of the job order costing method in calculating the cost of goods manufactured (COGM) at CV Karya Wenang Manado, a digital printing company specializing in calendar production. The research employed a qualitative descriptive approach with data collected through interviews, observation, and documentation. The findings indicate that the company’s current cost calculation is incomplete, particularly in allocating factory overhead costs, as depreciation and additional costs were not recorded. Using the job order costing method, the calculated COGM amounted to IDR 6,698,333 or IDR 13,400 per unit, compared to the company’s calculation of IDR 9,740,000 or IDR 19,480 per unit. This difference of IDR 3,041,667 demonstrates that the job order costing method provides a more accurate and efficient cost allocation, leading to a more realistic determination of selling price and higher profitability. The study contributes to the literature by emphasizing the importance of adopting appropriate cost accounting methods for small and medium enterprises in the printing industry.